2003
DOI: 10.1016/s0140-6736(03)13265-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a standard treatment protocol for severe acute respiratory syndrome

Abstract: A series of 31 patients with probable SARS, diagnosed from WHO criteria, were treated according to a treatment protocol consisting of antibacterials and a combination of ribavirin and methylprednisolone. Through experience with the first 11 patients, we were able to finalise standard dose regimens, including pulsed methylprednisolone. One patient recovered on antibacterial treatment alone, 17 showed rapid and sustained responses, and 13 achieved improvement with step-up or pulsed methylprednisolone. Four patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
269
3
6

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(283 citation statements)
references
References 4 publications
5
269
3
6
Order By: Relevance
“…41,42 In addition, some abietane-type diterpenes were also found to inhibit HIV-1 protease. 41,42 We observed that the specific abietane-type diterpenes (1)(2)(3)(4)(5)(6)(7)(8) possessed potent anti-SARS viral activities, but that these activities apparently did not involve action on 3CL protease because no 3CL protease inhibition was observed (data not shown). The molecular mechanism(s) by which these compounds operate needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 In addition, some abietane-type diterpenes were also found to inhibit HIV-1 protease. 41,42 We observed that the specific abietane-type diterpenes (1)(2)(3)(4)(5)(6)(7)(8) possessed potent anti-SARS viral activities, but that these activities apparently did not involve action on 3CL protease because no 3CL protease inhibition was observed (data not shown). The molecular mechanism(s) by which these compounds operate needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the most frequently administered antiviral and supportive treatment of SARS is a combination of ribavirin and corticosteroids. 4,5 Ribavirin, however, was only marginally effective against the SARS virus, and had serious adverse effects on SARS patients. 6,7 The combination therapy of HIV protease inhibitor drugs (lopinavir/ritonavir) plus ribavirin plus corticosteroids may improve some clinical outcomes, but only when administrated in the early phase of the illness.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in cytokine levels also correlated with improvement in general clinical condition, pulmonary function, and survival. 13,17 In view of rapid deterioration in lung function in many adult patients during the acute phase of SARS-CoV infection, 3,8 it would be deemed unethical to withhold corticosteroid treatment in any patients who had persistent fever or progressive radiographic changes at the onset of the outbreak. 8 Hence, all except 1 patient in this cohort were treated with corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, a dose-tapering course of oral prednisolone was prescribed in the following 2 weeks. This pediatric treatment regimen was extrapolated from the adult experience, 3,8 and the dose and timing of commencement of these medications were constantly under review during the outbreak.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation